Cost of chronic and episodic migraine patients in continuous treatment for two years in a tertiary level headache Centre - Negro, Andrea; Sciattella, Paolo; Rossi, Daniele; Guglielmetti, Martina; Martelletti, Paolo; Mennini, Francesco Saverio (Journal of headache and pain, 2019)
Background Migraine is one of the most common neurological diseases and an estimated 1.04 billion people worldwide have been diagnosed with migraine. Available data suggest that migraine is world widely associated with a high economic burden, but there is great variability in estimated costs that depends on the geographical, methodological and temporal differences between the studies. The purpose of this study was to quantify the annual direct cost of episodic migraine (EM) and chronic migraine (CM), both for the patient and for the National Health System (NHS), using data from subjects who attended an Italian tertiary headache centre. Furthermore, we evaluated comparatively the impact of gender and age on the economic burden of migraine. Methods We conducted a retrospective and non-interventional observational analysis of the electronic medical records of subjects with EM and CM who consecutively attended the Regional Referral Headache Centre of Rome and undergoing continuous treatment in the 2 years prior to 31 January 2019. This approach was intended to prevent distorsions due to natural fluctuations in migraine status over time. The collected data included demographic characteristics, number of specialist visits, consumption of medications, diagnostic tests, accesses in the emergency department (ED) and days of hospitalization due to the pathology. Results Our sample consisted of 548 patients (85.4% women and 14.6% men): 65.5% had CM and 34.5% had EM. The average annual expenditure per patient was €1482. 82.8% of the total cost (€1227) was covered by the NHS. The main item of expenditure were medications that represented 86.8% (€1286), followed by specialist visits (10.2%), hospitalizations for (1.9%), diagnostic tests for (1%) and ED visits for (0.1%). Costs were significantly higher for women than men (€1517 vs. €1274, p = 0.013) and increased with age ( p = 0.002). The annual direct cost of CM was 4.8-fold higher than that of EM (€2037 vs. €427, p = 0.001). Conclusion Our results provide a valuable estimate of the annual direct cost of CM and EM patients in the specific setting of a tertiary headache centre and confirm the high economic impact of migraine on both the NHS and patients.